A Pd@Zeolite Catalyst for Nitroarene Hydrogenation with High Product Selectivity by Sterically Controlled Adsorption in the Zeolite Micropores. Issue 33 (30th May 2017) - Zhang, Jian; Wang, Liang; Shao, Yi; Wang, Yanqin; Gates, Bruce C.; Xiao, Feng‐Shou
Abstract: The adsorption of molecules on metal nanoparticles can be sterically controlled through the use of zeolite crystals, which enhances the product selectivity in hydrogenations of reactants with more than one reducible group. Key to this success was the fixation of Pd nanoparticles inside Beta zeolite crystals to form a defined structure (Pd@Beta). In the hydrogenation of substituted nitroarenes with multiple reducible groups as a model reaction, the Pd@Beta catalyst exhibited superior selectivity for hydrogenation of the nitro group, outperforming both conventional Pd nanoparticles supported on zeolite crystals and a commercial Pd/C catalyst. The extraordinary selectivity of Pd@Beta was attributed to the sterically selective adsorption of the nitroarenes on the Pd nanoparticles controlled by the zeolite micropores, as elucidated by competitive adsorption and adsorbate displacement tests. Importantly, this strategy is general and was extended to the synthesis of selective Pt and Ru catalysts by fixation inside Beta and mordenite zeolites. Abstract : Pitaya‐like catalysts : Pd nanoparticles were fixed inside Beta zeolite crystals (Pd@Beta) to obtain a catalyst that displayed superior selectivity in the hydrogenation of substituted nitroarenes with multiple reducible groups. The high selectivity was attributed to the sterically controlled adsorption of the nitroarenes on the Pd nanoparticles within the zeolite micropores.